2016
DOI: 10.11648/j.aff.20160503.11
|View full text |Cite
|
Sign up to set email alerts
|

Socio Economic Conditions of the Hatchery Labors in Chanchra Area of Jessor District in Bangladesh

Abstract: Abstract:The study was conducted on the hatchery labors in some selected area of Jessore Sadar Upazila in Bangladesh under the district of Jessore by using a logical questionnaire on socio-economic condition of hatchery labor. The main objective of the study is to know the socio-economic condition of the hatchery labors in some selected area of Chanchra region of Jessore district. The specific objectives are to know the different labor categories in hatcheries of Chanchra region and to know the socio-economic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
3
2
0
Order By: Relevance
“…It was found that, there were 4 (8%) farmers produced 600-1000 kg/yr, 20 (40%) farmers produced 1001-2000 kg/yr, 9 (18%) farmers produced 2001-3000 kg/yr, and 17 (34%) farmers produced 3001kg -above/yr during the study. This production is more or less similar with the study of Siddika et al (2016); Hossain et al (2014); Akter (2001) and Ali et al (2015). The highest income was 33075000 Tk/yr and the lowest income from a pond was 20000 Tk/yr.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It was found that, there were 4 (8%) farmers produced 600-1000 kg/yr, 20 (40%) farmers produced 1001-2000 kg/yr, 9 (18%) farmers produced 2001-3000 kg/yr, and 17 (34%) farmers produced 3001kg -above/yr during the study. This production is more or less similar with the study of Siddika et al (2016); Hossain et al (2014); Akter (2001) and Ali et al (2015). The highest income was 33075000 Tk/yr and the lowest income from a pond was 20000 Tk/yr.…”
Section: Discussionsupporting
confidence: 91%
“…Which is similar with the findings of Asif et al (2015) and . It was found that 48 (96%) farmers were visited MBBS doctor or took allopathic treatment and only 2 (4%) of farmer were used to go to homeopathic treatment which is relevant with the findings of Zaman et al (2017); Siddika et al (2016); Islam et al (2014); ; ; Hossain et al (2014) and Ali et al (2015). From the survey, it was found that diseases, theft, shadow of trees, fallen leaves of tree, multiple ownership, lack of quality feed, lack of quality fish fry, water contamination by human baths and clothes washing, rapid water decrease in dry season, dike erosion in rainy season, snakes ate fishes in the pond etc were the major problems of fish production.…”
Section: Discussionsupporting
confidence: 57%
“…Kabir et al (2012) found that the highest (100%) fishermen of the old Brahmaputra River used tube-well water for drinking purposes, among them 40% had their own tube-well, 50% used shared tube-well and remaining 10% used neighbors tube-well. Same study conducted by Ali et al (2016); Asif et al (2015); Asif and Habib (2017); Hossain et al (2015); Sharif et al (2015); Rahman et al (2014); Vaumik et al (2017); Zaman et al (2017); Shabuj et al (2016); Siddika et al (2016)and Razeim et al (2017) also they have found the similar results.…”
Section: Discussionsupporting
confidence: 58%
“…This is not following the present study. Siddika et al (2016) reveals their study in Jessore district and found that maximum labor took nutrias food. After fish farming the highest number (57%) of fish farmer could eat 3 times meal per day.…”
Section: Discussionmentioning
confidence: 98%